2016
DOI: 10.1016/j.jsxm.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Amount of Testosterone on Laundered Clothing After Use of Testosterone Topical 2% Solution by Healthy Male Volunteers

Abstract: Introduction Testosterone 2% solution (Axiron) applied to armpit(s) is used for replacement therapy in men with a deficiency of endogenous testosterone. Aim To determine the amount of testosterone on subjects' T-shirts 12 hours after applying testosterone solution, the residual testosterone on subjects' T-shirts after laundering, and the testosterone transferred to unworn textile items during laundering with worn T-shirts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…One study identified a risk of transferring testosterone by clothing, 46 and another highlighted a risk of transferring topical products via bedding, 47 which adds a further complexity to the issue. Suitable alternative application sites would be the lower part of the belly, the groin or upper part of the thighs of human patients, which are already recommended in the product information for some THCP.…”
Section: Discussionmentioning
confidence: 99%
“…One study identified a risk of transferring testosterone by clothing, 46 and another highlighted a risk of transferring topical products via bedding, 47 which adds a further complexity to the issue. Suitable alternative application sites would be the lower part of the belly, the groin or upper part of the thighs of human patients, which are already recommended in the product information for some THCP.…”
Section: Discussionmentioning
confidence: 99%